Post-treatment of municipal wastewater for feeding to boilers using ionic exchange - Gutiérrez, Edixon; Caldera, Yaxcelys; Valbuena, Franz; Silva, Samuel (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The feasibility of the of ionic exchange process as treatment system of municipal wastewaters previously treated in a wastewater treatment plant, coming from the regions of Punta Cardón and Community Cardón. Punto Fijo, in the Falcon State, Venezuela, was studied with the purpose of produce water that fulfilled the physiochemical quality to be used in processes of vapor generation in a refinery. An experimental system composed by a cationic exchange with strongly acid resin (Amberlita IR-120) and anionic exchange with weakly basic resin (Amberlita IRA-58) were used. During the treatment, the following parameters were evaluated: conductivity, pH, alkalinity, total hardness (TD), dissolved total solids (DTS), calcium, magnesium, sodium, silica, chloride, bicarbonate and carbonate. The results demonstrated the technical feasibility of the ionic exchange process to treat municipal wastewater previously treated in a wastewater treatment plant to produce water that can be used as feeding to boilers of medium pressure. Total hardness valor was not appreciable after of treatment, while the valor of the ions Cl-, S04=, Si02, Na+, Ca+2, Mg+2 were lower that the tap water